THE USE OF LETTER CARD MEDIA IN IMPROVING BEGINNING READING SKILLS OF GRADE II STUDENTS AT MIS AL-ANWAR PRIVATE ELEMENTARY SCHOOL MEDAN - Atika Sari; Dewi Kusuma Nasution (Journal of Innovation in Research, Education and Culture (JIREC), 2026)
This study aims to improve the beginning reading skills of Grade II students at MIS Al-Anwar Private Elementary School Medan through the use of letter card media. Letter card media was chosen because it can attract students’ attention, help them recognize letters, and enable them to form words into meaningful reading. This study uses a Classroom Action Research (CAR) approach conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Data were collected through observation, interviews, and students’ reading tests. The results of the study show that the use of letter card media effectively improves students’ beginning reading skills. At the end of the second cycle, there was a significant improvement in students’ reading ability compared to the pre-cycle. In addition, students demonstrated higher motivation and interest in learning to read. Thus, letter card media is proven to be an effective and engaging tool in the process of teaching beginning reading skills.